Volume 99A, Number 8, August 2021 Cover Image. Issue 8 (11th August 2021) - Unknown
Abstract: Activation of antigen specific cytotoxic T lymphocytes requires a sequence of extra‐ and intracellular events and here Acyl, ATP citrate lyase, plays a central role as demonstrated by Vaughn and Haviland in a careful flow‐cytometric and expression study. (Read more in Vaughn and Haviland this issue include pp. 825–831)